Prevention of Stroke in Intracerebral Haemorrhage Survivors with Atrial Fibrillation: Rationale and Design for PRESTIGE-AF Trial - Korompoki, Eleni; Heuschmann, Peter; Harvey, Kirsten H.; Fiessler, Cornelia; Malzahn, Uwe; Hügen, Klemens; Ullmann, Sabine; Todd, Gabriele Putz; Schuhmann, Carolin; Montaner, Joan; Sibon, Igor; Debette, Stephanie; Enzinger, Christian; Ropele, Stefan; Rücker, Viktoria; Haas, Kirsten; Harvey, Emily; Wolfe, Charles; Wang, Yanzhong; Nielsen, Peter B.; Caso, Valeria; Lip, Gregory Y. H.; Lane, Deirdre A.; Halse, Omid; Ringleb, Peter; Haefeli, Walter E.; Foerster, Kathrin I.; Wurmbach, Viktoria S.; Veltkamp, Roland; on behalf of PRESTIGE-AF investigators (Thrombosis and Haemostasis, 2024)
Adequate secondary prevention in survivors of intracerebral hemorrhage (ICH) who also have atrial fibrillation (AF) is a long-standing clinical dilemma because these patients are at increased risk of recurrent ICH as well as of ischemic stroke. The efficacy and safety of oral anticoagulation, the standard preventive medication for ischemic stroke patients with AF, in ICH patients with AF are uncertain. PRESTIGE-AF is an international, phase 3b, multi-center, randomized, open, blinded end-point assessment (PROBE) clinical trial that compared the efficacy and safety of direct oral anticoagulants (DOACs) with no DOAC (either no antithrombotic treatment or any antiplatelet drug). Randomization occurred in a 1:1 ratio and stratification was based on ICH location and sex. The two co-primary binary endpoints included ischemic stroke and recurrent ICH which will be analyzed hierarchically according to the intention-to-treat principle. Secondary efficacy endpoints encompassed all-stroke and systemic embolism, all-cause and cardiovascular mortality, major adverse cardiac events, and net clinical benefit. Secondary safety endpoints included any major hemorrhage and intracranial hemorrhage. All outcome events were adjudicated by an independent committee. Results of PRESTIGE-AF are expected to support risk-adjusted secondary prevention in ICH survivors with AF and to inform clinical guideline recommendations.
Keywords: intracerebral hemorrhage; atrial fibrillation; ischemic stroke; randomized controlled trial; direct oral anticoagulants